PENGEMBANGAN MODUL PENERIMAAN KARYAWAN DAN MODUL PENGGAJIAN PADA SISTEM INFORMASI KEPEGAWAIAN PT. TRAKTOR NUSANTARA BANDAR LAMPUNG - Astria Hijriani; Febi Eka Febriansyah; Ana Ana (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
This study developed a Decision Support System (DSS) by utilizing Analytical Hierarchy Process (AHP) Method as a process in selection of employees acquisition. This selection process used several criteria (multicriteria) to choose which applicants will be accepted. This Decision Support System (DSS) helps managers of Human Resources (HR) in deciding which applicants will be selected. In this application, there are criteria used and the weight of those criteria. This application of module business process will be able to generate the rank of each applicant based on the final amount. The applicant who has the greatest value will be given a better rank and it means that the applicant has criteria in accordance with company’s requirement. In addition, Web Service as a business process of payroll modules. In this process, a set of functions or methods which contained on a server can exchange data and information using an operating system and application that different from each other through the internet that uses XML as the format of message delivery. This system constructed by using PHP and MySQL as language. The result of functional testing data based on test case testing shows that the system can work